2002
DOI: 10.1097/00130478-200210000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Alternative arterial catheterization site using the ulnar artery in critically ill pediatric patients

Abstract: Based on the ischemic and infectious complication rates, the ulnar artery should be considered as a viable site for peripheral vessel cannulation in cases in which arterial catheterization is necessary and attempts at more common sites of catheterization are unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Kahler and Mirza [3] considered the ulnar artery as a safe alternative for peripheral arterial cannulation in 18 critically ill pediatric patients. In their series, only one patient with ulnar cannulation showed signs of ischemia, and this patient previously had ipsilateral radial artery cannulation for 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kahler and Mirza [3] considered the ulnar artery as a safe alternative for peripheral arterial cannulation in 18 critically ill pediatric patients. In their series, only one patient with ulnar cannulation showed signs of ischemia, and this patient previously had ipsilateral radial artery cannulation for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Many anesthesiologists consider radial artery cannulation as the standard technique for hemodynamic monitoring among the upper extremity arteries [2]. There is a tendency to choose the ulnar artery if the radial artery is unsuitable for cannulation [3]. The radial artery is the dominant vessel of the hand [4].…”
Section: Introductionmentioning
confidence: 99%
“…151 Slogoff et al 16 reported no hand ischemia in 22 patients who had an ulnar artery catheter placed after a failed radial artery cannulation. 149 Although there is a theoretical concern that ulnar artery cannulation could cause neural trauma to the ulnar nerve, the literature lacks evidence of such a complication. 153 Hand ischemia has been reported in pediatric patients with prolonged ulnar artery cannulation in the setting of prior radial artery cannulation.…”
Section: Ulnar Artery Cannulationmentioning
confidence: 99%
“…Because of the risk of ischemia to the hand, placement of a catheter in the ulnar artery is contraindicated if the radial artery is thrombosed or after attempts at cannulation have been made. Despite concerns of distal ischemia, a literature report indicates a similar risk for ulnar, radial, and femoral arterial lines [ 104 ].…”
Section: Sites For Invasive Monitoringmentioning
confidence: 99%